A short stay unit decreased mean length of stay in a hospital in south Brazil - Furlanetto, Tania Weber; Barcelos, Daniel de Souza; Faulhaber, Gustavo Adolpho Moreira (Clinical and Biomedical Research, 2014)
Introduction Public health services in Brazil are periodically overcrowded. Since reducing the length of stay (LOS) could increase the availability of hospital beds, this study evaluated the impact of a short stay unit (SSU) on LOS, early readmission rates, and intra-hospital mortality rates. Methods Data were evaluated retrospectively in the 12 months before and after the establishment of a multidisciplinary SSU in a tertiary care hospital in south Brazil. All admissions of adult patients through the Emergency Department for causes in nine groups of the World Health Organization International Code of Diseases-10 were included. Results Mean LOS decreased 1.42 days in the first year after the implementation of a SSU with no change in 7-day readmission rates or intra-hospital mortality rates. This decrease may be partially explained by the decrease in the mean LOS in other areas of the hospital, although the amount of hospital-bed days saved in the second year was 5,668 days in the Internal Medicine Division and 1,595 days in all other clinical or surgical areas. Mortality rates after discharge were not evaluated. Conclusions A SSU decreased mean LOS of selected patients admitted through the Emergency Department without increasing 7-day readmission rates or intra-hospital mortality.